2019
DOI: 10.1371/journal.pcbi.1006819
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale modeling of influenza A virus replication in cell cultures predicts infection dynamics for highly different infection conditions

Abstract: Influenza A viruses (IAV) are commonly used to infect animal cell cultures for research purposes and vaccine production. Their replication is influenced strongly by the multiplicity of infection (MOI), which ranges over several orders of magnitude depending on the respective application. So far, mathematical models of IAV replication have paid little attention to the impact of the MOI on infection dynamics and virus yields. To address this issue, we extended an existing model of IAV replication in adherent MDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…Similar effects have been described for the Aureococcus anophagefferens -Brown Tide virus (AaV) where a saturation of infection was observed at a MOI of 8 [75]. Furthermore, a recent study modeling the replication of Influenza A virus in cell culture demonstrated that at high MOIs the number of defective interfering particles (DIPs) present in the inoculum plays a greater role [76]. DIPs have been shown to compete with intact virus particles for cellular resources, and therefore may significantly reduce viral replication [77].…”
Section: Discussionmentioning
confidence: 56%
“…Similar effects have been described for the Aureococcus anophagefferens -Brown Tide virus (AaV) where a saturation of infection was observed at a MOI of 8 [75]. Furthermore, a recent study modeling the replication of Influenza A virus in cell culture demonstrated that at high MOIs the number of defective interfering particles (DIPs) present in the inoculum plays a greater role [76]. DIPs have been shown to compete with intact virus particles for cellular resources, and therefore may significantly reduce viral replication [77].…”
Section: Discussionmentioning
confidence: 56%
“…Nevertheless, a few systematic large-scale experiments aimed at looking at the entire process of viral infection in model organisms have been performed [303], and we predict that they will lead the way to wider uses of the 'alternative system' that may ultimately lead to a deeper understanding of the virus and its pathogenicity and to a better treatment or vaccination. While the traditional models of influenza have their advantages and usefulness, we believe that the alternative models must be used in parallel.…”
Section: Discussionmentioning
confidence: 99%
“…Expression was normalized to the β-actin reference gene levels, while relative expression was calculated using the comparative method of 2-∆∆Ct. The virus replication curve was quanti ed and normalized by using virus copy numbers (Rüdiger et al 2019;Frensing et al 2016). Changes in gene expression were examined by t-test, and p < 0.05 was considered signi cant.…”
Section: Western Blottingmentioning
confidence: 99%